IDEAL trial: economic analysis - de Portu, Simona; Montella, Sabato; Menditto, Enrica; Cammarota, Simona; Citarella, Anna; Mantovani, Lorenzo G. (Farmeconomia. Health economics and therapeutic pathways, 2008)
Introduction: the IDEAL (“High-dose atorvastatin vs usual-dose simvastatin for secondary prevention after myocardial infarction”) study was carried out to compare intensive lowering of low-density lipoprotein (LDL)-cholesterol using the highest recommended dose of atorvastatin 80 mg with simvastatin 20 mg. Aim: our aim was to investigate the economic consequence of high dose of atorvastatin vs usual-dose of simvastatin in reducing major coronary events in patients with a history of acute myocardial infarction (AMI). Methods: the analysis is based on clinical outcome data from the IDEAL study. We conducted a cost-effectiveness analysis, comparing high dose of atorvastatin (80 mg/die) versus usual-dose of simvastatin (20 mg/die) in the perspective of the Italian National Health Service. We identified and quantified medical costs: drug costs according to the Italian National Therapeutic Formulary and hospitalizations were quantified based on the Italian National Health Service tariffs (2008). Effects were measured in terms of morbidity reduction (frequency of hospitalizations). We considered an observation period of 4.8 years. The costs borne after the first 12 months were discounted using an annual rate of 3%. We conducted one and multi-way sensitivity analyses on unit cost and effectiveness. Results: the cost of atorvastatin therapy over the 4.8 years period amounted to approximately 2.4 millions euro per 1,000 patients. The total cost of atorvastatin high dose was about 3.9 millions euro, the incremental cost per patient free from event is 31.176,03 euro. Discussion: this evaluation found that atorvastatin therapy is cost-effective. Results were sensitive to either clinical or economic variables.